The Impossibility of Return: Güney Dal and the Exilic Condition (Konturen, 2020)
This article examines the role exile plays in the works of the first generation of Turkish German authors by focusing on Güney Dal. The first part of the article deals with Güney Dal’s interviews with other Turkish German authors in 1983. Even though the authors interviewed by Dal do not consider themselves exiles, I show that exilic consciousness is marked not only by the impossibility of returning home, a condition that the authors interviewed deny sharing with exiles, but also by the fact that the exilic subject is already displaced within and is as such unable to be at home. In the second part, I interpret Dal’s novel Eine Kurze Reise nach Gallipoli (1994), which he wrote after moving back to Turkey, as a work that showcases this insurmountable uprootedness and argue that Dal’s modernist novel shows that the disintegration of exilic consciousness can establish a link with political and ethical issues beyond the reach of the isolated and paranoid subject.